تقييم صلاحية مياه سد الباسل لأغراض الشرب والري - يونس ســـوسن (Latakia University Journal -Engineering Sciences Series, 2019)
تضمن البحث إجراء التقييم لبعض التحاليل الدورية الفيزيائية – الكيميائية (الجمالية) والجرثومية للمياه من ثلاثة مواقع مائية موزعة في بحيرة السد الواقعة في محافظة طرطوس ولمدة عامين كاملين، اعتباراً من كانون الثاني عام 2001 ولغاية كانون الأول 2002 ، حيث تم قياس (درجة الحرارة، الناقلية الكهربائية، درجة الحموضة ال PH) والشوارد السالبة (CL-، ، )، والشوارد الموجبة (، ، )، في مواقع الرصد بالعلاقة مع العوامل الخارجية. حيث تبين من نتائج التحليل ارتفاع تراكيز (، ) في المواقع المذكورة وارتفاع عدد (F.C) عن الحدود التي سمحت بها المواصفة القياسية السورية لمياه الشرب، وتوصلنا بعد مناقشة النتائج إلى مجموعة استنتاجات وتوصيات، يحتاج الأخذ بها وتطبيقها بشكل متكامل إلى إدارة سليمة لجودة المياه السطحية. وأهم هذه الاستنتاجات، هي عدم صلاحية مياه السد بوضعها الحالي لأغراض الشرب نتيجة ارتفاع شوارد (، ) و(F.C) عن الحدود التي سمحت بها المواصفة القياسية السورية لمياه الشرب. أما بالنسبة لمياه بحيرة السد فهي صالحة للري غير المقيد ولكنها غير صالحة للري المقيد بسبب ارتفاع تعداد (F.C) حسب منظمة الصحة العالمية. The research includes evaluation of some periodic physical-chemical (Aesthetics) and bacterial analyses of water in three locations on the Dam’s Lake in Tartous Governorate, for two full years, starting from January 2001 through December 2002 ; The temperature, electricity conductability, acidity degree (PH), negative ions (CL-، ، ), and positive ions (، ، ) have been measured in the observation locations in relation to the external factors. results of Analysis shown that concentrations of (، ) and the number of (F.C) in the mentioned locations are in excess of the limits tolerated by the Syrian Standards for drinking water. After discussing the results, we have reached a set of conclusions and recommendations for a sound management of surface water quality. The most important conclusion is that the dam’s water in its current status is not fit for drinking purposes because the Ions (، ) and (F.C) exceed the limits tolerated by the Syrian Standards for drinking water. As for the water of the lake, it is fit for unrestricted irrigation, but not fit for restricted irrigation due to the high number of (F.C) in accordance with to World Health Organization.